Utilization of Medicinal Plants by the Tapos Village Community, Cijeruk District, Bogor Regency - Naily Fitrotun Ni’mah; Ukhradiya Magharaniq Safira Purwanto; Syamsul Falah (Institut Pertanian Bogor, 2025)
The diversity of medicinal plant species in Tapos Village has the potential to be developed. However, studies on medicinal plants are still limited. This study aimed to inventory the types of ethnophytomedica, their efficacy, and their utilization by residents of Tapos Village, Cijeruk District, Bogor Regency. This research is expected to provide a reference for further research and efforts to increase public understanding of medicinal plants. Data were collected through several stages: literature study, observation, unstructured interviews, and documentation. The results of this study showed that as many as 39% of the 99 types of medicinal plants were dominated by herbal habitus. The most widely used parts are the leaves (60 %) and cultivated medicinal plants (59 %). Most types of plants are used to cure a group of gastrointestinal diseases, with as many as 23 types of plants. The people of this village maintain local wisdom in utilizing medicinal plants. Keywords: Ethnophytopharmaca, medicinal plants, Tapos Village